The contribution of Polluter Pays Principle (PPP) approach on environmental pollution reduction and health risk for Municipal Solid Waste (MSW) - Ikmal Irozi, Mohd Filza; Syed Ismail, Sharifah Norkhadijah; Sarva, Mangala Praveena; Shamsuddin, Aida Soraya; Che Dom, Nazri (Springer Cham, 2022)
This study estimated the contribution of the polluter pays principle (PPP) on the reduction of environmental pollution and health risk for municipal solid waste (MSW). Data of MSW volume disposed (tonnes) in the landfill from 2011 to 2017 were obtained from the respective agency. The level of GHG emission (CH4, CO2), leachate production, heavy metals, on-methane organic compound (NMOC), and health risks were calculated using the mathematical equation for three PPPs implementation scenarios. The average volume of waste disposed in the landfill was 199,593.48 ± 16,094.14 tonnes/year. The volume has increased by 29.4%, from 14,912.80 ± 821.17 tonnes/month in 2011 to 19,300.47 ± 829.44 tonnes/month in 2017. Prediction on waste composition was made based on the average percentage provided by the National Solid Waste Management Department (NSWMD). Food waste dominates in household waste composition (57,472.94 ± 4634.30 tonnes/year) followed by institutional, commercial, and industrial waste composition (21935.32 ± 1768.75 tonnes/year). The emission of CH4 and CO2 in scenario 1 were 6058.96 tonnes/year and 151,473.88 tonnes/year, in scenario 2 were 5193.39 tonnes/year and 145,414.93 tonnes/year, and in scenario 3 were 4327.83 tonnes/year and 121,179.11 tonnes/year; respectively. The volume of leachate produced in scenario 1, scenario 2, and scenario 3 were 29,340.24 m3, 25,148.78 m3, and 20,957.32 m3, respectively. The total heavy metals production in leachate in scenario 1, scenario 2, and scenario 3 were 1.26 kg/year, 1.08 kg/year, and 0.901 kg/year, respectively. The total production of non-methane organic compounds (NMOCs) in scenario 1, scenario 2 and scenario 3 were 2.93E-01 m3, 2.52 E-01 m3, and 2.09E-01 m3, respectively. The implementation of PPP has the potential to reduce environmental pollution and health risk by reducing the total waste disposed in the landfill.